Effectiveness of high‐frequency left prefrontal repetitive transcranial magnetic stimulation in patients with treatment‐resistant depression: A randomized clinical trial of 37.5‐minute vs 18.75‐minute protocol. Issue 3 (25th June 2019) - Kito, Shinsuke; Miyazi, Midori; Nakatani, Honoka; Matsuda, Yuki; Yamazaki, Ryuichi; Okamoto, Tatsuya; Igarashi, Yoshio
Abstract: Aim: Clinical trials and meta‐analyses have demonstrated the efficacy of high‐frequency repetitive transcranial magnetic stimulation (rTMS) over the left prefrontal cortex in treatment‐resistant depression. The aim of this study was to prospectively evaluate the effectiveness of the conventional 37.5‐minute vs 18.75‐minute rTMS protocol over the left prefrontal cortex in patients with treatment‐resistant depressive episode. Methods: Thirty patients with treatment‐resistant depression or bipolar disorder depressive episode were randomized 1:1 to either 37.5‐minute or 18.75‐minute rTMS protocol groups. rTMS treatment was applied at 120% resting motor threshold with 10 Hz over the left prefrontal cortex. Treatment sessions were delivered for a total of 3000 pulses/d, 5 days a week, for 4‐6 weeks. Patients received a 75 trains with "4 sec on and 26 sec off" for 37.5 minutes or a 75 trains with "4 sec on and 11 sec off" for 18.75 minutes. Severity of depression was rated with the Quick Inventory of Depressive Symptomatology (QIDS) and Patient Health Questionnaire (PHQ‐9). Remission was defined as a total score of 5 or less on the QIDS. The primary outcome measure was to compare the remission rate between the both groups. Results: Thirteen of 30 patients (43.3%) showed remission at week 6. There were no significant differences in the remission rate between the conventional 37.5‐ and 18.75‐minute protocol groups (46.7% and 40.0%, respectively). No seizures or treatment‐emergent mania/hypomania were occurred. Conclusion: These findings suggest that, compared with the conventional one, rTMS with 18.75‐minute protocol might be equally effective and clinically beneficial in saving the treatment session length. Further well‐designed studies are needed. Abstract : Effectiveness of rTMS in treatment‐resistant depression: a randomized clinical trial of 37.5‐minute vs 18.75‐minute protocol